1994
DOI: 10.1017/s0021932000021477
|View full text |Cite
|
Sign up to set email alerts
|

Subsistence ecology and carrying capacity in two Papua New Guinea populations

Abstract: SummaryThis article examines the mechanisms of subsistence adaptation of two Papua New Guinea populations, the Metroxylon sago-depending lowland Gidra and the taro-monoculture Mountain Ok, surviving in low population densities of 0·5 and 1·4 persons per km2. Observation of the groups' land use systems strongly suggests that their population densities have not been far below the carrying capacity, although the territory of each population is markedly heterogeneous. Both groups have maintained their sustainable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It is reported that the carrying capacity of sago is not very high in PNG (Ohtsuka 1994) and that sago cannot support the human population, especially if population pressures increase significantly. On the contrary, it is argued that sago palm has a very high starch production potential, and higher than the other crops, such as cassava, sweet potatoes, and potatoes.…”
Section: Sago Use As Foodmentioning
confidence: 99%
“…It is reported that the carrying capacity of sago is not very high in PNG (Ohtsuka 1994) and that sago cannot support the human population, especially if population pressures increase significantly. On the contrary, it is argued that sago palm has a very high starch production potential, and higher than the other crops, such as cassava, sweet potatoes, and potatoes.…”
Section: Sago Use As Foodmentioning
confidence: 99%
“…Studies in Papua New Guinea have shown the utility of reconstructing patterns of population increases over a period of one century using genealogical information [23]. Historical demographic processes have significant impacts on the social institutions that embed indigenous common property regimes such as CST.…”
Section: Sea Tenurementioning
confidence: 99%
“…In contrast, in large parts of CNG, people practised a virtual monoculture dominated by taro. 10 Their gardening regimes involved shorter cycles of shifting cultivation with a series of plantings being made throughout the year, providing gardens at various stages of maturity (Ohtsuka 1994). Over the last four or five decades, however, there has been an increasing reliance on sweet potato which, unlike taro, matures within a single year, thrives above 1,500 metres, can grow on lower valley slopes and floors that have poor soils unsuitable for taro, and provides excellent pig fodder (Eggertsson 2003: 19-22;Hyndman & Morren 1990;Jones 1980: 11-6;Kuchikura 1990;Morren 1986: 90-100, Poole 1976.…”
Section: The Languages Of the Study Areamentioning
confidence: 99%
“…Access to land for gardening or hunting and gathering determined the position of the settlement. All settlements had a defined territory with land dedicated to horticulture and to hunting and the gathering of wild resources (Huber 1980: 45;Morren 1986: 249;Ohtsuka 1994). There were significant ecological constraints determining settlement size, most importantly the nature of rainforest soil, which is usually exhausted after a year of cropping.…”
Section: Settlement Typesmentioning
confidence: 99%